2010
DOI: 10.5539/jas.v2n2p174
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Manipulation of Rumen Fermentation Efficiency by Fumaric acid – Bentonite Coupled Addition as an Alternative to Antibiotics

Abstract: Short term in vitro incubations were used to evaluate the effect of fumaric acid -bentonite coupled addition on rumen fermentation effeciency. Ruminal contents from five steers were used for preparation of inoculums of mixed rumen microorganisms that were used in generatation of three treatment systems, negative control, fumaric acid treated, and fumaric acid -bentonite coupled treated. The fermentation pattern revealed that, this coupled addition was associated with an additional increase in propionic acid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
5
0
2
Order By: Relevance
“…In the past few decades, feed additives such as antibiotics were used in ruminant production for optimization of the rumen fermentation pattern and to improve feed intake and efficiency ( Abdl-Rahman, 2010 ; Patra, 2011 ). However, presently most of these supplements are not used routinely because of toxicity problems in the host animals and microbial adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, feed additives such as antibiotics were used in ruminant production for optimization of the rumen fermentation pattern and to improve feed intake and efficiency ( Abdl-Rahman, 2010 ; Patra, 2011 ). However, presently most of these supplements are not used routinely because of toxicity problems in the host animals and microbial adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal value of NGR in the rumen is about 3.5, and a value lower than 3.5 indicates more efficient utilization of SCFA for gluconeogenesis (Abdl-Rahman, 2010). In the current study, TB supplementation had no effect on the fermentation pattern in ewes indicated by the fairly constant NGR, which is consistent with previous research (Kowalski et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A influência de adsorventes de natureza argilosa como a montmorilonita sobre indicadores de fermentação ruminal foi investigada em outros estudos [1,2,[17][18][19]. A redução na quantidade de metano (CH4) em 24 h, observada no presente estudo, possivelmente foi decorrente da menor atividade das bactérias metanogênicas.…”
Section: Discussionunclassified
“…A MMT induziu a diminuição da viabilidade de protozoários responsáveis em abrigar bactérias metanogênicas, prejudicando a relação de simbiose dessas bactérias com a população de protozoários [18]. A redução significativa da quantidade de amônia (NH3) pode ser relacionada à capacidade de armazenamento de NH3 pela MMT ou pela redução da atividade proteolítica dos protozoários [1]. A adição de 0,75% de MMT na dieta de ovinos, alimentados com alto teor de grãos, aumentou a quantidade de AGCC e o pH ruminal foi estabilizado mais próximo da neutralidade [19].…”
Section: Discussionunclassified